Urgency of Mutual Insurance Policy Guarantee Program in Indonesia - Mediawati Noor Fatimah; Multazam Mochammad Tanzil; Amanda Filia (E3S Web of Conferences)
The inclusion of the policy guarantee program in the Omnibus Law, specifically Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector, represents a significant advancement for the Indonesian public, particularly for policyholders, including those holding mutual insurance policies. The Deposit Corporation is designated as the institution responsible for implementing this program. Considering the ongoing challenges faced by mutual insurance companies in Indonesia, such as Bumiputera 1912, the immediate realization of this program is crucial. This research aims to analyze the urgency of implementing a mutual insurance policy guarantee program in Indonesia. The study employs a normative juridical research method supported by a comprehensive literature review. In conclusion, this study highlights the urgency of implementing a mutual insurance policy guarantee program in Indonesia, which serves to: (1) rebuild public trust in the insurance industry; (2) restore stability in the financial sector; (3) create opportunities for the growth of the insurance industry; (4) provide support to struggling insurance companies to prevent their collapse; (5) uphold the constitutional mandate as outlined in the 1945 Constitution; and (6) safeguard the interests of policyholders while adhering to the mandate of the International Association of Insurance Supervisors (IAIS).